What Can DNA Exonerations Tell Us about Racial Differences in Wrongful Conviction Rates? - David J. Bjerk; Eric Helland (Institute of Labor Economics (IZA), 2018)
We examine the extent to which DNA exonerations can reveal whether wrongful conviction rates differ across races. We show that under a wide-range of assumptions regarding possible explicit or implicit racial biases in the DNA exoneration process (including no bias), our results suggest the wrongful conviction rate for rape is substantially and significantly higher among black convicts than white convicts. By contrast, we show that only if one believes that the DNA exoneration process very strongly favors innocent members of one race over the other could one conclude that there exist significant racial differences in wrongful conviction rates for murder.
Keywords: K4; 330; DNA evidence; wrongful convictions; justice; discrimination